(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Ahara, Nidra and Brahmacharya plays significant role in preventing major diseases affecting both physical and mental well-being. Nidra stands out as one of the prominent factors to be examined in the contemporary era, constituting a vital component of a healthy lifestyle. Ayurveda defines Nidra (sleep) as the physiological state of rest for the Sharira (body), Mana (mind) and Indriya (sense organs). Lack of Nidra, results in conditions like primary insomnia or Anidra and is associated with the onset of various clinical diseases. Over time, it progress into chronic disorders such as secondary or tertiary insomnia. Aim: To introduce and underscore the concept of Nidra and its physiological impact on the human body. Materials and Method: The literature review was compiled from available Ayurvedic literatures and various relevant articles related to Nidra and sleep. Conclusion: Ayurveda has given more importance to Nidra (sleep) by considering it as one among three pillars of life. The Samhitas provide an in-depth exploration of Nidra, presenting its classification and physiology. Nidra (sleep) is not just a phenomenon to ignore but it has great impact in our body and the study of sleep phenomenon is important for the early diagnosis of sleep disorders.